(untitled) (Global Journal of Science Frontier Research, 2014)
The present study was designed to test the effect of AM fungi in aggregating the soil particles against their dispersion at various levels of salt stress (L1 -1.5dSm-1; L2 -3.0dSm-1; L3 -4.5dSm-1) in the rhizosphere of onion. Soil quality parameters such as organic carbon content (0.61 per cent), microbial biomass carbon (327.0 mg kg -1), glomalin 119.33 (μg/ g of soil) and aggregate stability (53 per cent) were highly influenced by AM fungal inoculations. The soil bulk density and particle density were slightly brought down (1.34 and 2.52 per cent respectively) with increase in the water holding capacity and porosity (78.94 and 51.83 per cent respectively) even at third level of salt stress. In most of the cases the sodic soil isolates performed on par with the standard isolates which proved the efficacy of the isolates to compete with the standard cultures in bringing up the soil health.